Effect of Maggot on the IL-6 and IFN-Ɣ Expression of Koi Fish (Cyprinus carpio) Infected with Edwardsiella tarda - Ida Ayu Kade Wimala Niti; Maftuch Maftuch; Rahmi Nurdiani (Journal of Aquaculture and Fish Health, 2023)
The increase in koi fish cultivation can lead to increase risks and caused problems. The main problem is high disease attacks caused by the bacteria Edwardsiella tarda. One of the alternatives to control the disease is immunostimulant treatment with the use of maggot, Hermetia illucens Larvae, known as Black Soldier Fly (BSF). This study aims to report the effect of maggot as a substitute for koi fish feed formulations on the immune system of koi fish infected with E. tarda. This study used a descriptive method, by quantitative approach with the IL-6 and IFN-Ɣ expression through RT-PCR analysis and fish survival rate (%). Identification of E. tarda was carried out by the PCR test method at a molecular weight of 200 bp. The density of bacteria that caused the death of the 50% koi fish population (LD50) for 72 hours was 107 cells/ml. The highest IL-6 expression in the spleen was found in sample C of 28,844 and the lowest in-sample K (+) of 26,096. The highest IL-6 expression in the liver was in sample K (+) of 29,060 and the lowest was in sample D of 25,428. The highest IFN-Ɣ in the spleen was in treatment C, 28,844, and the lowest was in treatment D, 27,219. The highest IFN-Ɣ in liver was sample K (+) of 26,795, and the lowest in-sample C of 25,615. The survival rate of fish in this study reached 30%-100%. The optimal amount of substitution of maggot treatment is 75% (Treatment C) of fish feed.